Bilateral Carotid-Cavernous Fistula: A Diagnostic and Therapeutic Challenge. (April 2022) - Sharma, Rohan; Ponder, Christian; Kamran, Mudassar; Chacko, Joseph; Kapoor, Nidhi; Mylavarapu, Krishna; Onteddu, Sanjeeva; Nalleballe, Krishna
Carotid-cavernous fistula (CCF) is an aberrant communication between the main trunk or branches of carotid artery and the cavernous sinus. Most of the cases of CCF occur following head trauma, but congenital and spontaneous cases have been reported. We report an interesting case of bilateral CCF with no history of trauma, thus most likely spontaneous form. Since it is rare, it was a diagnostic challenge. The suspicion of this diagnosis was made due to clinical features of headache, signs of increased Intracranial Pressure (ICP) (nausea, vomiting, and worsening headaches during Valsalva), exophthalmos, periorbital edema, periorbital erythema, chemosis, and conjunctival injection in both eyes. It was diagnosed with a 4-vessel angiography (digital subtraction angiography) which is the gold standard and was managed successfully with endovascular coil embolization.